Thermal Structure and Composition of Saturn's Upper Atmosphere From Cassini/Ion Neutral Mass Spectrometer Measurements. Issue 20 (16th October 2018) - Yelle, Roger V.; Serigano, J.; Koskinen, T. T.; Hörst, S. M.; Perry, M. E.; Perryman, R. S.; Waite, J. Hunter
Abstract: Analysis of measurements of the H2 density in Saturn's equatorial thermosphere indicates temperatures from 340 to 370 K. The deepest measurements, obtained during Cassini's final plunge into the atmosphere, measure the thermospheric temperature profile. The measurements are well fit by a Bates profile with an exospheric temperature of 354 K and a temperature gradient at 1.2 × 10 −4 Pa of 0.4 K/km, corresponding to a thermal conduction flux of 7.3 × 10 −5 W/m 2 . The helium profiles are consistent with diffusive equilibrium. The CH4 profiles are not in diffusive equilibrium but instead have a roughly constant mixing ratio relative to H2 . We interpret this as the signature of a downward external flux of ∼10 13 m −2 s −1 . Saturn's rings are the most likely source of this external material. Plain Language Summary: The mass spectrometer on the Cassini spacecraft measured the densities of molecular hydrogen, helium, and methane, among other species, along the spacecraft track through the atmosphere. Analyzing these data determines the temperature structure of the upper atmosphere. We find temperatures of 340 to 370 K. We also find that the methane in the upper atmosphere comes from Saturn's rings rather than the lower atmosphere. Key Points: Cassini INMS measured the distribution of H2, He, and CH4 in Saturn's equatorial thermosphere The exospheric temperature varies from 340 to 370 K The CH4 distribution indicates an external flux of ∼10 13 m −2 s −1